Essentials of the living world - Johnson, George B (McGraw-Hill Higher Education, 2006)
Includes index.; In this basic concepts version of our very successful The Living World, George Johnson has provided the fundamentals to understanding biology in a more condensed format while still integrating analogies and current issues which makes science relevant to the student. George Johnsonâ€™s textbook has often been considered a student favorite. Dr. Johnson has written this non-majors textbook from the ground up to be an engaging and accessible learning tool with an emphasis on "how things work and why things happen the way they do". This authoritative textbook features a straightforward, clear writing style and a wide variety of media assets to enhance the content of the textbook.The strength of this textbook is the integration of many tools that are designed to inspire both students and instructors. The multi-media package for the text stretches students beyond the confines of the traditional textbook to include high interest video clips and animations of key biological concepts; Quỹ Châu Á